Manufactured Volvulus - Zweifel, Noemi; Meuli, Martin; Subotic, Ulrike; Moehrlen, Ueli; Mazzone, Luca; Arlettaz, Romaine (European Journal of Pediatric Surgery, 2013)
Background/Purpose Malrotation with a common mesentery is the classical pathology allowing midgut volvulus to occur. There are only a few reports of small bowel volvulus without malrotation or other pathology triggering volvulation. We describe three cases of small bowel volvulus in very premature newborns with a perfectly normal intra-abdominal anatomy and focus on the question, what might have set off volvulation.Methods In 2005 to 2008, three patients developed small bowel voluvulus without any underlying pathology. Retrospective patient chart review was performed with special focus on clinical presentation, preoperative management, intraoperative findings, and potential causative explanations. Mean follow-up period was 46 months.Results All patients were born between 27 and 31 weeks (mean 28 weeks) with a birth weight between 800 and 1,000 g (mean 887 g). They presented with an almost identical pattern of symptoms including sudden abdominal distension, abdominal tenderness, erythema of the abdominal wall, high gastric residuals, and radiographic signs of ileus. All of them were treated with intensive abdominal massage or pelvic rotation to improve bowel movement before becoming symptomatic.Conclusions Properistaltic maneuvers including abdominal massage and pelvic rotation may cause what we term a “manufactured” volvulus in very premature newborns. Thus, this practice was stopped.
Keywords: volvulus; premature newborns; malrotation; abdominal massage